2021
DOI: 10.3390/ijerph18168848
|View full text |Cite
|
Sign up to set email alerts
|

Pain Neuroscience Education Combined with Therapeutic Exercises Provides Added Benefit in the Treatment of Chronic Neck Pain

Abstract: Background: Chronic neck pain is common in the adult general population. Although the etiology of chronic neck pain is under debate, it is clear that chronic neck pain is multifactorial, with both physical and psychosocial contributors. Objective: To determine whether adding pain neuroscience education (PNE) to therapeutic exercises improved their pain–disability index, pain catastrophizing, fear–avoidance beliefs, and pain self-efficacy in subjects with chronic nonspecific neck pain. Methods: This study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 49 publications
4
37
0
3
Order By: Relevance
“…The physiotherapists in this study recommended a variety of treatments to manage both acute and chronic nociceptive and neuropathic types of pain. The efficacy of many of the treatments is supported in the literature, such as exercise (Polaski et al 2019 ), pain neuroscience education (Javdaneh et al 2021 ), TENS (Bi et al 2015 ; Celik et al 2013 ; Gibson et al 2017 ) and neural tissue mobilisation (Su & Lim 2016 ). We agree with Hagen and Rekand ( 2015 ) that the management of pain should be based on clinical findings so that the correct type of pain is diagnosed (Hagen & Rekand 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physiotherapists in this study recommended a variety of treatments to manage both acute and chronic nociceptive and neuropathic types of pain. The efficacy of many of the treatments is supported in the literature, such as exercise (Polaski et al 2019 ), pain neuroscience education (Javdaneh et al 2021 ), TENS (Bi et al 2015 ; Celik et al 2013 ; Gibson et al 2017 ) and neural tissue mobilisation (Su & Lim 2016 ). We agree with Hagen and Rekand ( 2015 ) that the management of pain should be based on clinical findings so that the correct type of pain is diagnosed (Hagen & Rekand 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been observed that women use more medication for symptoms of pain, anxiety and depression than men [ 15 ]. Several studies concluded that the addition of pain education to manual therapy can be a very useful intervention in patients with CP [ 21 ]. From a clinical point of view, the differences between groups in pain intensity, psychological distress and kinesiophobia may help to establish new clinical criteria for the diagnosis and treatment of CGD, TTH and MCNP.…”
Section: Discussionmentioning
confidence: 99%
“…A knowledge of whether psychological distress and kinesiophobia are present in the previously defined groups and a comparison of these characteristics between the groups could help clinicians to improve the wellbeing of patients. It has been observed that pain education can provide benefits for the treatment of CP [ 21 ]; if there are differences between groups, the treatment and education provided can be emphasized, based on the differences found.…”
Section: Introductionmentioning
confidence: 99%
“…Catastrophizing belief patterns such as "pain is terrifying," or, "I'll never recover from this or regain my earlier capabilities," and other emotional issues contribute to increased levels of pain perception, which in turn increases the feedback loop of pain severity (41). There is evidence that educating patients about the relationship between their brain, body, and pathways of pain leads to greater recovery, especially when combined with therapeutic exercises (42)(43)(44). Without education on pain, and especially for those that have low thresholds for pain sensitivity, catastrophizing can lead to slower recovery rates and greater levels of pain interpretation.…”
Section: Evidence Overview 411 Pain Pathwaysmentioning
confidence: 99%